2021
DOI: 10.15376/biores.16.3.4693-4703
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of heat treatment parameters’ effect on some physical and mechanical properties of poplar wood with multi-criteria decision making techniques

Abstract: Effects of the heat treatment parameters were evaluated relative to some physical and mechanical properties of poplar wood (Populus alba L.) with use of two of the prominent multi criteria decision-making (MCDM) techniques: Entropy and The Technique for Order Preference by Similarity to Ideal Solution (TOPSIS). To meet this objective, the test samples were heat-treated at 120, 150, 180, and 210 °C for 2 and 4 h in a laboratory-scale oven. With increasing temperature and duration, the shrinkage and swelling rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
0
7
0
1
Order By: Relevance
“…Generally, the criteria (tests) in this study are used to determine whether the wood material is suitable for the place of use. Kaymakci and Bayram [46] used the same criteria (tests) to measure the success of the heat treatment and to determine the optimum parameters.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, the criteria (tests) in this study are used to determine whether the wood material is suitable for the place of use. Kaymakci and Bayram [46] used the same criteria (tests) to measure the success of the heat treatment and to determine the optimum parameters.…”
Section: Resultsmentioning
confidence: 99%
“…They noted that the dimensional stability of Japanese cedar wood improved as the temperature and treatment duration increased leads to decrease in shrinkage coefficient. Kol (2010) and Kaymakci (2021) has also reported that the values of volumetric shrinkage decreases in thermally modified Pine, Fir and Poplar wood, treated at 190, 212°C for 2 h and 210°C for 4 h.…”
Section: Shrinkage Coefficient Of Woodmentioning
confidence: 93%
“…For beech (Fagus orientalis Lipsky) wood thermally modified under atmospheric pressure in almost all modification variants (for temperatures of 150 • C, 175 • C, 200 • C and time of 1 h, 3 h, 5 h), the authors obtained an increase in the value of compressive strength contained between 2.98% and 19.3%. A slight decrease in compressive strength at the level of 1.16% was shown only in the case of beech wood modified at 200 • C for 5 h. Kaymakci and Bayram [48] obtained an increase in the CS for poplar wood (Populus alba L.) after modification at the temperatures of 120 • C, 150 • C, 180 • C for 2 h and 4 h under atmospheric pressure. The highest (i.e., 14%) increase in the CS value was obtained after the modification of poplar wood at a temperature of 120 • C for 2 h. However, the decrease in the CS value was recorded only for the highest modification temperature, i.e., 210 • C and the times of 2 h and 4 h, with the maximum decrease in CS at the level of 22% for 210 • C and 4 h. The decrease in compressive strength can be reduced by using a closed system with an inert gas such as nitrogen or steam [34].…”
Section: Modification Time (H)mentioning
confidence: 97%